THE STORY OF MORAL CHARACTER: MORALITY, NARRATIVE, AND THE VALUE OF STRIVING - Black, Jessica (My University, 2018)
The purpose of this investigation was to expand on the limited extant research exploring what people take into consideration when they judge the moral character of others. Specifically, I examined the preference for moral conflict or striving (vs. lack of temptation) across the domains of morality outlined in Haidt’s (2007) Moral Foundations Theory (Graham et al., 2011), and investigated how moral character judgment relates to individual differences in morality and relevant constructs, as well as lifetime exposure to literature. Results suggest that, at least for these domains of moral behavior, people tend to judge targets who are not tempted to act immorally more moral than those who are tempted, but behaved in a moral manner anyway. However, there were significant differences in response between individual domains. The vast majority of participants found people who did not have to strive to do the right thing more moral in the domains of fairness and care, whereas far more participants found striving to overcome temptation more moral in the domains of authority, loyalty, and purity. In general, higher scores on measures that assess morally relevant constructs were associated with preferences for lack of temptation; increased exposure to both fiction and nonfiction tended to be associated with preferences for striving to overcome internal conflict. Results are discussed with reference to prior research, study limitations, and future directions for the investigation of moral character judgment.
Keywords: Moral Character Judgment; Moral Psychology; Moral Foundations Theory